Peran Keuangan Bump Basmallah Dalam Pemulihan Perekonomian Pasca Pandemi Di Pondok Pesantren Roudlotul Huda Magetan Perspektif Maqashid Syariah - Kalimah, Siti; Nafi'ah, Nafi'ah; Fathoni, Khoirul (Journal of Sharia Economic Law, 2024)
The background to this research is that the Roudlotul Huda Magetan Islamic Boarding School contains Islamic Boarding School-Owned Enterprises (BUMP) which play an important role in the Islamic boarding school's economy. The presence of Covid-19 caused the economy to decline, and this thesis contains the problem formulation, (1) How is the application of maqashid syari'ah in the economic recovery of BUMP Basmallah at the Roudlotul Huda Islamic Boarding School, Magetan?, (2) How is the application of maqashid syari'ah to BUMP Basmallah's financial role in post-pandemic economic recovery at the Roudlotul Huda Islamic Boarding School, Magetan? This research was conducted using a qualitative research approach with data collection procedures and through interview, observation and documentation techniques. The conclusions are (1) Implementation of maqashid syari'ah at BUMP Basmallah in economic recovery at the Roudlotul Huda Magetan Islamic Boarding School by fulfilling the objectives of maqashid syari'ah in accordance with the level of need, namely the dharuriyyah (primary needs), (2) Application of maqashid syari'ah in post-pandemic economic recovery at the Roudlotul Huda Islamic Boarding School by fulfilling aspects of the maqashid shari'ah elements, namely maintaining religion, soul, reason and protecting property. So that it can achieve its goals according to the provisions prescribed by Islam